Determination of the drag coefficient during the first and second gliding positions of the breaststroke underwater stroke - Vilas-Boas, J. P.; Costa, L.; Fernandes, R. J.; Figueiredo, P. A.; Marinho, D. A.; Silva, A. J.; Rouboa, A. I.; Machado, L. (Journal of Applied Biomechanics, 2010)
The purpose of the current study was to assess and to compare the hydrodynamics of the first and second gliding positions of the breaststroke underwater stroke used after starts and turns, considering drag force (D), drag coefficient (CD) and cross-sectional area (S). Twelve national-level swimmers were tested (6 males and 6 females, respectively 18.2 ± 4.0 and 17.3 ± 3.0 years old). Hydrodynamic parameters were assessed through inverse dynamics from the velocity to time curve characteristic of the underwater armstroke of the breaststroke technique. The results allow us to conclude that, for the same gliding velocities (1.37 ± 0.124 m/s), D and the swimmers` S and CD values obtained for the first gliding position are significantly lower than the corresponding values obtained for the second gliding position of the breaststroke underwater stroke (31.67 ± 6.44 N vs. 46.25 ± 7.22 N; 740.42 ± 101.89 cm2 vs. 784.25 ± 99.62 cm2 and 0.458 ± 0.076 vs. 0.664 ± 0.234, respectively). These differences observed for the total sample were not evident for each one of the gender`s subgroups.